COST OF ILLNESS DIABETES MELITUS TIPE 2: NARRATIVE REVIEW - Nadia Pramasari; Dwi Endarti; Anna Wahyuni Widayanti (Universitas Muhammadiyah Magelang, 2022)
Diabetes mellitus (DM) is chronic disease that requires routine lifelong treatment. Uncontrolled blood sugar levels in DM patients can cause complications. This has an impact on the burden of health costs. The aim of this study to conduct a narrative review of the cost of illness in type 2 DM patients in various countries. The English articles used in this study were obtained from Pubmed, ScienceDirect, and Wiley that published in the period 2011 to 2021. The cost reported in the articles were local currency that later converted into US dollars according to the time of the study. Based on the narrative review, there are 19 articles that meet the criteria. In the article, there are varied perspectives, methods, and cost categories. The total cost per year for type 2 DM ranged from US246.1 to US5894.1, direct, and indirect costs per patient per year ranged from US 104.6 to US5246.4 and US82.9 to US2299.4. Type 2 diabetes mellitus increases the burden of health costs. The presence of complications in type 2 DM patients requires higher health costs compared to uncomplicated type 2 DM patients and non-DM patient